IMPLEMENTATION OF AREFI TO IMPROVE BASIC KNOWLEDGE OF EFI - Komarudin Komarudin; Widiyanti Widiyanti; Mahfudi Sahly Subandi; Dianna Ratnawati; Sudirman Rizki Ariyanto; Tiwit Nor Hidayat; Achmad Chairuddin; Risca Zahra Permatahat (STKIP PGRI Tulungagung, 2025)
Many students do not demonstrate optimal mastery because EFI mate-rial is considered complex and abstract, while conventional learning using engine stands has limited accessibility outside school hours. This innovation is designed to create an immersive learning experience fo-cused on reinforcing foundational knowledge regarding the identifica-tion of components, functions, and the operational flow of the EFI sys-tem. The study employs a quantitative method with a quasi-experimental design of the Non-equivalent Control Group Design type. The research sample consisted of 80 students in the 11th grade of Light Vehicle Engineering, divided into an experimental group and a control group. Data were collected through pre-tests and post-tests, then ana-lysed using ANOVA with a significance level of α=0.05. The results of the study indicate that the use of AREFI media has a significant posi-tive impact on student learning outcomes. There was an increase in the average score from 44.73 in the pre-test to 70.92 in the post-test. The ANOVA test results showed an F value of 90.217 with a significance level of 0.000 (p < 0.05), proving that the difference in learning out-comes between the two groups was caused by the use of the AREFI media. Therefore, it can be concluded that the AREFI learning media has proven to be effective as an innovative solution for visualizing abstract EFI concepts, enhancing interaction, and facilitating deep un-derstanding among vocational high school students.